Changes in diet quality and food security among adults during the COVID-19–related early lockdown: results from NutriQuébec. Issue 4 (5th January 2021) - Lamarche, Benoît; Brassard, Didier; Lapointe, Annie; Laramée, Catherine; Kearney, Michèle; Côté, Mélina; Bélanger-Gravel, Ariane; Desroches, Sophie; Lemieux, Simone; Plante, Céline
ABSTRACT: Background: The impact that the coronavirus disease 2019 (COVID-19)–related early lockdown has had on dietary habits of the population and on food insecurity is unknown. Objective: The aim of this study was to document the change in diet quality and in food insecurity observed during the COVID-19–related early lockdown. We hypothesized that the lockdown was associated with a deterioration in overall diet quality and an increase in food insecurity. Methods: Data are from a COVID-19 subsample of NutriQuébec, a web-based cohort destined to study temporal changes in dietary habits among adults in Quebec, Canada. Participants completed questionnaires before (between June 2019 and February 2020) and during (April to May 2020) early lockdown, including a validated web-based 24-h recall ( n  = 853) and a questionnaire on food security ( n  = 922). Primary study outcomes were temporal changes in diet quality measured by the Healthy Eating Index (HEI)–2015 and in the prevalence of food insecurity. Results: There was a small increase in the HEI-2015 during the COVID-19 early lockdown compared with baseline (+1.1 points; 95% CI: 0.6, 1.5), mostly due to small improvements in the intakes of whole grains, greens and beans, refined grains, total vegetables, total dairy, seafood and plant proteins, added sugar, and total protein subscores of the HEI-2015. Exploratory analyses suggested that individuals aged 18–29 y (+3.6 points; 95% CI: 2.4, 4.7), participants with lower education (+1.9 points; 95% CI: 1.3, 2.6), or with obesity (+3.8 points; 95% CI: 2.7, 4.8) showed particularly important increases in the HEI-2015. The prevalence of food insecurity was reduced from 3.8% at baseline to 1.0% during the early lockdown (prevalence ratio = 0.27; 95% CI: 0.08, 0.94). Conclusions: Contrary to our hypotheses, diet quality has slightly improved and prevalence of food insecurity was reduced in this sample of adults from Quebec during the COVID-19–related early lockdown. These results may be generalizable only to relatively healthy populations.